P433 An interesting case diagnosed as both phenylketonuria and maternal phenylketonuria. (June 2019) - Öz, Sibel; Kor, Deniz; Kılavuz, Sebile; Bulut, Fatma Derya; Yılmaz, Berna Şeker; Demir, Fadli; Kartal, Tuğçe Özakçaoğlu; Yıldırım, Gözde Atasever; Neslihan Önenli Mungan, Halise
Abstract : Introduction: Phenylketonuria (PKU) is the most common and autosomal recessively inherited metabolic disease due to the deficiency of phenylalanine hydroxylase (PAH). Elevated levels of phenylalanine are not only toxic for the children but also teratogenic for the fetus. Clinical findings of maternal phenylketonuria (MPKU) are intrauterine growth retardation, microcephaly, significant developmental delay, congenital cardiac anomalies, and some other structural defects. Poorly diet control and high levels of blood phenylalanine causes to this severe but preventable clinical syndrome. Case report: A seven-day-old girl admitted to the pediatric metabolism clinic with a suspicion of PKU after newborn screening program. She was born at 40 weeks of gestation with a 2300 gr birth weight and hospitalized for 2 days. Her parents were first degree cousins and the family history was unremarkable for an inherited metabolic disease, however the mother had two miscarriages. Physical examination revealed microcephaly, mild facial dysmorphism, and cardiac murmur in addition to intrauterine growth retardation. Her blood phenylalanine level was 1140 µmol/dL and she was diagnosed as moderate phenylketonuria. As a ventricular septal defect was detected with echocardiography and the mother was born before the national newborn screening program was available, the mother's blood Phe concentration was measured. Surprisingly her blood Phe level was 1614 µmol/dL. The mother was a 25 years old woman be able to graduate from primary school and. complained about only concentration problems and forgetfulness. She had also blond hair and blue eyes on physical examination. Conclusion: Maternal phenylketonuria is a preventable public health problem which causes undesirable results like mental-motor retardation and cardiac defects. Although maternal phenylketonuria is not completely coped with, after newborn screening program the incidence is decreased. A strict Phe restricted diet beginning before the pregnancy together with frequent controls of blood Phe levels are essential for management. Here, we report this case, as she was diagnosed both phenylketonuria and maternal phenylketonuria and in order to emphasize thinking MPKU in the presence of microcephaly, developmental delay, and cardiac defects. Maternal phenylketonuria, newborn screening program, developmental delay.